2013
DOI: 10.1002/anie.201308005
|View full text |Cite
|
Sign up to set email alerts
|

A Microgel Construction Kit for Bioorthogonal Encapsulation and pH‐Controlled Release of Living Cells

Abstract: pH-Cleavable cell-laden microgels with excellent long-term viabilities were fabricated by combining bioorthogonal strain-promoted azide-alkyne cycloaddition (SPAAC) and droplet-based microfluidics. Poly(ethylene glycol)dicyclooctyne and dendritic poly(glycerol azide) served as bioinert hydrogel precursors. Azide conjugation was performed using different substituted acid-labile benzacetal linkers that allowed precise control of the microgel degradation kinetics in the interesting pH range between 4.5 and 7.4. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
167
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 153 publications
(171 citation statements)
references
References 53 publications
3
167
0
1
Order By: Relevance
“…In the past decade, a tremendous effort has been directed to develop intelligent drug nanocarriers that release their payload in response to intrinsic intracellular signals, particularly to endosomal/lysosomal pH and cytoplasmic glutathione (GSH) [24][25][26]. Polymeric components with pH-sensitive groups (pH-induced protonation/deprotonation or degradation) are used to produce drugformulation nanosystems that are relatively stable in the circulation but also have the ability to rapidly release the entrapped drugs in the tumor tissue (pH 6.8) as well as in the intracellular compartments, such as endosomes (pH 5.5-6) and lysosomes (pH 4.5-5.0) of cells [27][28][29]. Following escape from the endosome and by taking advantage of the high redox potential in cytoplasms and nuclei of cancer cells, which have much higher concentration of reducing glutathione (GSH) tripeptide than body fluids and extracellular milieu (0.5-10 mM versus 2-20 μM GSH), reduction-sensitive nanosystems containing S-S bonds have been designed and exploited for active cytoplasmic release of various potent chemotherapeutics [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, a tremendous effort has been directed to develop intelligent drug nanocarriers that release their payload in response to intrinsic intracellular signals, particularly to endosomal/lysosomal pH and cytoplasmic glutathione (GSH) [24][25][26]. Polymeric components with pH-sensitive groups (pH-induced protonation/deprotonation or degradation) are used to produce drugformulation nanosystems that are relatively stable in the circulation but also have the ability to rapidly release the entrapped drugs in the tumor tissue (pH 6.8) as well as in the intracellular compartments, such as endosomes (pH 5.5-6) and lysosomes (pH 4.5-5.0) of cells [27][28][29]. Following escape from the endosome and by taking advantage of the high redox potential in cytoplasms and nuclei of cancer cells, which have much higher concentration of reducing glutathione (GSH) tripeptide than body fluids and extracellular milieu (0.5-10 mM versus 2-20 μM GSH), reduction-sensitive nanosystems containing S-S bonds have been designed and exploited for active cytoplasmic release of various potent chemotherapeutics [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…For the metal-free click reaction, chitosan and hyaluronan were modified with oxanorbor- 30 nadiene (OB) and 11-azido-3,6,9-trioxaundecan-1-amine (AA), respectively. The gelation is attributed 31 to the triazole ring formation between OB and azido groups of polysaccharide derivatives. The molecular 32 structures were verified by FT-IR spectroscopy and elemental analysis, giving substitution degrees of 58% 33 and 47% for chitosan-OB and hyaluronan-AA, respectively.…”
mentioning
confidence: 98%
“…Typically, 1,3-dipolar cyclo-addition cat-64 alyzed by Cu (I) can be accomplished with high efficiency, 65 reliability, and no by-products under the physiological condition 66 [21][22][23][24][25][26][27][28][29]. Some macromolecular derivatives, such as poly(vinyl 67 alcohol) (PVA) [18], polyethylene glycol (PEG) [21,23,26,28] and 68 hyaluronan [20,27] [31,32]. Presently, the SPPC has been employed to graft bioactive 86 peptides to PEG hydrogels for molecular patterning [33,34].…”
mentioning
confidence: 99%
“…The broad applicability of these materials was demonstrated by successful cell culturing of a range of cells, such as fibroblasts, human mesenchymal stem cells, and bone marrow derived stromal cells. [30][31][32][33] When culturing cells on hydrogels, it is important to understand how they interact with their surroundings. It has been stated that cells are able to feel the substrate they are attached to and that they will respond based on these external mechanical signals.…”
Section: Introductionmentioning
confidence: 99%
“…[34,35] For example, it has been shown that the differentiation of mesenchymal stem cells is dependent on substrate stiffness. Culturing on soft gels (0.1-1 kPa) led to neurons, but myoblasts were formed on stiffer substrates (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and cells differentiated into osteoblasts on rigid matrices (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). [36] Recent research indicates that these stem cells retain their phenotype on a non-fouling zwitterionic hydrogel, independent of stiffness.…”
Section: Introductionmentioning
confidence: 99%